Effect of high hydrostatic pressure processing on textural properties and microstructural characterization of fresh‐cut pumpkin (Cucurbita pepo). (30th January 2020) - Hu, Xinna; Ma, Tao; Ao, Le; Kang, Huan; Hu, Xiaosong; Song, Yi; Liao, Xiaojun
Abstract: High hydrostatic pressure (HHP) processing is a burgeoning nonthermal sterilization technology has been industrialized in foreign countries. The purpose of this research was to investigate HHP (100–600 MPa/2 min)‐induced texture and cell microstructural changes of fresh‐cut pumpkins compared with untreated and heated samples. Treatment efficacy was evaluated by texture profile analysis and combinational microscopy techniques, including transmission electron microscope (TEM) and confocal imaging. The results showed that the texture of pumpkin was jointly influenced by HHP‐triggered alterations in pectin characteristics, membrane completeness, and morphology of tissue. Samples subjected to HHP treatment could better maintain original histology properties than heated ones based on color parameter, hardness, relative electrical conductance, and degree of pectin esterification, among which moderate pressure (300–400 MPa) exerted more positive effects. Our findings provide theoretical guidance for the correlative application of HHP and promote further investigation on food varieties. Practical Applications: HHP processing is a commercially implemented technology being used in vegetable‐based products. As an important factor highly correlated with freshness, texture alterations induced by processing are an industrial issue of great concern. This work provides new evidence on the softening mechanism comprehensively with respect to pectin, membrane, and morphology of tissue. The application of our current findings could be applied in other temperature‐sensitive food substrates and make it possible to produce products of high quality in mild temperature. Abstract :